2005
DOI: 10.1038/sj.jcbfm.9600222
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) Accumulation and Enhancement of Postischemic Brain Damage in 110-kDa Poly(ADP-ribose) Glycohydrolase Null Mice

Abstract: Poly(ADP-ribose) (PAR) is a polymer synthesized by poly(ADP-ribose) polymerases (PARPs) and metabolized into free adenosine diphosphate (ADP)-ribose units by poly(ADP-ribose) glycohydrolase (PARG). Perturbations in PAR synthesis have been shown to play a key role in brain disorders including postischemic brain damage. A single parg gene but two PARG isoforms (110 and 60 kDa) have been detected in mouse cells. Complete suppression of parg gene causes early embryonic lethality, whereas mice selectively lacking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 63 publications
1
60
1
Order By: Relevance
“…Interestingly, the splice variants reported here encode PARG proteins that are devoid of the putative regulatory A-domain. Functions of this domain are not yet well understood, but its absence in the PARG Δ2-3/Δ2-3 mouse is responsible for a complex phenotype of hypersensitivity against genotoxic stress [18] and the loss of the three large PARG proteins results in cytotoxic cerebral [20] and splanchnic [21] accumulation of cellular PAR after ischemiareperfusion injury, illustrating its importance in regulating PARG activity, and thus PAR turnover. Recently, it has been reported that PARG physically interacts with PARP-1, regulating its activity and that both form a complex with XRCC1 after MNNG induced DNA damage [57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the splice variants reported here encode PARG proteins that are devoid of the putative regulatory A-domain. Functions of this domain are not yet well understood, but its absence in the PARG Δ2-3/Δ2-3 mouse is responsible for a complex phenotype of hypersensitivity against genotoxic stress [18] and the loss of the three large PARG proteins results in cytotoxic cerebral [20] and splanchnic [21] accumulation of cellular PAR after ischemiareperfusion injury, illustrating its importance in regulating PARG activity, and thus PAR turnover. Recently, it has been reported that PARG physically interacts with PARP-1, regulating its activity and that both form a complex with XRCC1 after MNNG induced DNA damage [57].…”
Section: Discussionmentioning
confidence: 99%
“…In this model, AIF released from the mitochondria rapidly translocates to the nucleus and activates an endonuclease facilitating chromatinolysis and cell death in a caspase-independent manner [61][62][63]. While it is possible that NAD+ depletion as a result of PAR formation may affect the mitochondrial membrane potential ( [64,65] ), there also is accumulating evidence that PAR itself may be acting as a cell death signaling molecule triggering the formation of a mitochondrial pore transition (MPT) in a yet unknown way [66]. Moreover, it has been shown that monomeric ADP-ribose (ADPR) produced by activation of PARP/PARG enzymes contributes to oxidative stress induced cell death by specifically activating the cell membrane Ca 2+ channel TRPM2 by binding to its nudix motif [67,68] and, hypothetically, the novel PARG isoforms could contribute to the release of ADPR from the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that KO mutant mice are hypersensitive to lipopolysaccharide-induced septic shock (Cortes et al, 2004) as well as to postischemic brain damage (Cozzi et al, 2005). Because PARP-1 can still be activated in KO mutant mice but with a low degree of automodification, DNA damage-induced cell death pathway may become prominent in this model.…”
Section: Discussionmentioning
confidence: 99%
“…9 Infarcts were measured 3 days after MCAO to rule out transient neuroprotection. The anti-PAR antibody and the Caspase-3 activity determination kit were from Alexis, the anti-PARP-1, and anti-caspase-3 antibodies were from Cell Signaling.…”
Section: Methodsmentioning
confidence: 99%